PERTANGGUNGJAWABAN PIDANA PELAKU PENGALIHAN OBJEK JAMINAN FIDUSIA TANPA PERSETUJUAN TERTULIS DARI PENERIMA FIDUSIA (Studi Putusan Nomor: 56/Pid.Sus/2019/PN Mnd) - Nikolas F Sagala; Herlina Manullang; July Esther (Jurnal Visi Eksakta, 2023)
The crime of transferring the object of fiduciary security is a crime in the field of fiduciary security which iscarried out by selling the object of the fiduciary security which has not yet been paid off by the payment creditto a third party without written approval from a company as the recipient of the fiduciary. The problems in thisstudy are how the criminal liability of the perpetrator of the transfer of the object of fiduciary security withoutwritten consent from the fiduciary recipient (Study of Decision No.56/Pid.Sus/2019/PN Mnd) and how thejudge's considerations are based in imposing sanctions on the perpetrator of the transfer of the object. fiduciaryguarantee without written consent from the fiduciary recipient (Study of Decision No.56/Pid.Sus/2019/PNMnd).The Legal Research Method used in this thesis is a normative juridical method, namely the analysis carried outto collect data by means of a literature study. This study uses primary legal materials, namely Law Number 42of 1999 concerning Fiduciary Guarantees and this study also uses secondary legal materials in the form ofjournal publications on law and various related literature to answer problems in the Study of Decision No.56/Pid. Sus/2019/PN Mnd.Based on the results of research conducted in the Study of Decision Number 56/Pid.Sus /2019/PN Mnd, it canbe concluded that based on the judge's considerations in imposing a crime against the perpetrator who transferred the object of fiduciary security without written consent from the fiduciary recipient, the defendanthas fulfilled the elements and violates Article 36 of Law No. 42 of 1999 concerning Fiduciary Guarantees,he is sentenced to imprisonment for 7 (seven) months and a fine of Rp. 10,000,000 (ten million rupiah) with theprovision that if the fine is not paid, it is replaced with imprisonment for 2 (two) months.